Implementation of E-MP to Support the Promoter Program in the Jurisdiction of Sumedang Police Department - Sectio Aristo, Galih (Advances in Police Science Research Journal, 2024)
Along with the times in utilizing information technology, the government, especially the National Police, brought new ideas in conducting investigations through the Promoters program. The National Police Criminal Investigation Agency launched an application called e-Management Investigation (e-MP) regulated in Perkap Number 6 of 2019. The factors that influence why this e-MP is not working as planned include the basic factors of the law itself, the law enforcers namely investigators in the use of e-MP, facilities and infrastructure in the use of e-MP, investigator culture in the use of e-MP, and community factors. The e-MP application has been used by Sumedang Regional Police since 2018. This e-MP was initially socialized to members of the Sumedang Regional Police investigator by the Criminal Investigation Police. The implementation of e-MP itself in Sumedang District Police continues to increase every month and this e-MP is very helpful for superiors to determine policies and monitor the performance of members and make it easier for members themselves to process investigative data. . Sumedang Police Investigator in inputting the data on the progress of the investigation is just logged into the website robinops.bareskrim.polri.go.id continue to fill in the data on the website and then the data is stored by the Criminal Investigation Police. This application is in line with the Promoter program, which is to create a professional, modern and reliable National Police. The public can see and monitor the progress of the results of investigations through the e-MP application by opening the SP2HP application online or PUSIKNAS, so the community reports their incident to the investigator, then the investigator will socialize about the use of the e-MP application.